Functional molecular interfaces for impedance-based diagnostics - Kanyong, P; Patil, AV; Davis, JJ (Annual Reviews, 2020)
In seeking to develop and optimize reagentless electroanalytical assays, a consideration of the transducing interface features lies key to any subsequent sensitivity and selectivity. This review briefly summarizes some of the most commonly used receptive interfaces that have been employed within the development of impedimetric molecular sensors. We discuss the use of high surface area carbon, nanoparticles, and a range of bioreceptors that can subsequently be integrated. The review spans the most commonly utilized biorecognition elements, such as antibodies, antibody fragments, aptamers, and nucleic acids, and touches on some novel emerging alternatives such as nanofragments, molecularly imprinted polymers, and bacteriophages. Reference is made to the immobilization chemistries available along with a consideration of both optimal packing density and recognition probe orientation. We also discuss assay-relevant mechanistic details and applications in real sample analysis.